A Rare Case of Sudden Death in a Patient with Takotsubo Cardiomyopathy Secondary to Cardiac Rupture - Tarun Dalia; Bashar S. Amr; Ankit Agrawal; Archana Gautam; Venkata Rakesh Sethapati; Jared Kvapil (Case Reports in Cardiology)
Takotsubo cardiomyopathy (TCM), also known as broken heart syndrome or stress-induced cardiomyopathy, is a rare condition with an estimated incidence of 0.02% of all hospitalizations in United States and 2% of all acute coronary syndrome presentations. TCM predominately presents as a transient wall motion abnormality of the left ventricular apex due to emotional or physical stress. Cardiac rupture in the setting of TCM is an extremely rare phenomenon with limited published case reports. We present a case of a 75-year-old female who had cardiac rupture secondary to TCM and performed a literature review using Ovid MEDLINE for published cases showing this association. After the literature review, we found 20 cases showing this association, which are listed in a tabular fashion.